2015
DOI: 10.1177/0891988715598237
|View full text |Cite
|
Sign up to set email alerts
|

Visual Priming and Visual Hallucinations in Parkinson’s Disease. Evidence for Normal Top-Down Processes

Abstract: Background: Visual hallucinations (VH) are common in Parkinson's disease (PD) and are associated with increased morbidity and mortality. Current explanations for VH in PD suggest combined impairments in top-down attentional and bottom-up perceptual processes, which allow the passive ''release'' of stored images. Alternative models in other disorders have suggested that top-down factors may actively encourage hallucinations. In order to explore the interaction between top-down and bottom-up visual processing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
8
2
Order By: Relevance
“…The current study aimed to extend the findings of Straughan et al (2016) and Yokoi et al (2014) by assessing differences between patients with and without hallucinations and by adding associative priming to experimentally examine the effects of environmental factors.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The current study aimed to extend the findings of Straughan et al (2016) and Yokoi et al (2014) by assessing differences between patients with and without hallucinations and by adding associative priming to experimentally examine the effects of environmental factors.…”
Section: Introductionmentioning
confidence: 94%
“…Consistent with these models, combined impairments in top-down and bottom-up processes are risk factors for visual hallucinations in LBD (Barnes & Boubert, 2008; Bronnick, Emr, Tekin, Haughen, & Aarsland, 2011; Gallagher, Parkkinen, O’Sullivan, Spratt, Shah et al, 2011; Imamura, Wada-Isoe, Kitayama, & Nakashima, 2008; Meppelink, De Jong, Teune, & Van Laar, 2009; Ozer, Meral, Hanoglu, Ozturk, Cetin et al, 2007; Ramírez-Ruiz, Junqué, Martí, Valldeoriola, & Tolosa, 2006, 2007; Straughan, Collerton, & Bruce, 2016). This focus on factors within participants, however, neglects potential interactions with the environment and does not provide an explanation of why hallucinatory episodes tend to occur at specific times and locations and to be tightly integrated with the visual environment (Collerton, Taylor, Tsuda, Fujii, Nara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…128132 A dopaminergic basis of VH and other perceptional disorders is being researched. A cortico-striato-thalamocortical dysfunction has been suggested, 89,133,134 however at present, work is required to determine and distinguish the differing forms of hallucinations.…”
Section: Nmss Domain 4: Perceptional Disordersmentioning
confidence: 99%
“…The scrambled images were used to assess whether PD-VH patients are prone to report real objects while none is physically present. Since recent studies suggested that the usage of visual illusions might contribute to the sensitivity detecting Parkinson patients with hallucinations (Shine et al., 2012; Straughan et al., 2016), we also implemented a Continuous Flash Suppression condition (CFS) that suppresses salient stimuli from perceptual awareness due to binocular rivalry (Stein et al., 2011; Tsuchiya and Koch, 2005).…”
Section: Introductionmentioning
confidence: 99%